Pharmacogenetics role in the safety of acenocoumarol therapy - Jiménez-Varo, Enrique; Cañadas-Garre, Marisa; Henriques, Cristina Isabel; Pinheiro, Ana Margarida; Gutiérrez-Pimentel, María José; Calleja-Hernández, Miguel Ángel (Thrombosis and Haemostasis, 2014)
Vitamin K antagonists (VKAs) remain as the most prescribed drug for treatment and prevention of thrombotic disorders in many countries, despite the recent approval of the new oral anticoagulants (NOACs). Although effectiveness and safety of VKAs are tightly associated to maintaining the patient within the international normalised ratio (INR) therapeutic range (TWR), they have been likened to NOACs when patients are in good INR control (≥66% of TWR). Therefore, assessing the safety of patients should be a priority in the selection of the anticoagulation therapy. The aim of this study was to evaluate the association between CYP2C9*2, CYP2C9*3, VKORC1, CYP4F2*3, ABCB1 C3435T, APOE, CYP2C19*2 and CYP2C19*17 gene polymorphisms and treatment safety in 128 patients diagnosed with atrial fibrillation or venous thromboembolism during the initial first seven months of acenocoumarol therapy. After the first month, VKORC1-Tallele and APOE-E3/E3 genotype were independently associated to higher time above therapeutic range (TAR) and lower time below the therapeutic range (TBR). After seven months, VKORC1 T-allele predicted higher TAR, and was also associated to increased INR>4, particularly the TT-genotype (odds ratio [OR]: 32; 95% confidence interval [CI95%]: 6–175; p=810–5). C-alleles for CYP2C9*3 (OR: 5.5; CI95%: 1.8–17; p=0.003) and ABCB1 (OR: 8.9;CI95%: 1.1–70; p=0.039) independently influenced on INR>6 . Patients VKORC1-TT/ABCB1-C remained 26.8% [19.7–38.9] TAR, with associated relative risk (RR) for INR>4 1.8 higher (CI95%: 1.2–2.5; p=0.015). Patients VKORC1-TT also presented the highest risk of bleeding events (RR: 3.5;CI95%: 1.4–8.4; p=0,010). In conclusion, VKORC1, CYP2C9*3, APOE and ABCB1 genotypes should be considered in prevention of overanticoagulation and bleeding events in the initiation of acenocoumarol therapy.
Keywords: Pharmacogenetics; VKORC1; safety; CYP2C9; atrial fibrillation; acenocoumarol